2015
DOI: 10.1002/sca.21225
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between frictional force and surface roughness of orthodontic archwires

Abstract: Lateral force microscopy measures the lateral bending of the cantilever depending on the frictional force acting between the tip and surface. The aim of this study was to investigate and compare the relationship between the surface roughness and frictional resistance of four archwire and bracket combinations consisting of the 0.016-inch NiTi and 0.019 × 0.025-inch stainless steel archwires interacting clinically with two representative self-ligating brackets, active-type Clippy-C(®) ceramic self-ligating brack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…The results of the present study showed that the highest surface roughness was noted with Tefloncoated NiTi, followed by NiTi and CuNiTi, while the lowest surface roughness was noted for SS. These findings are in accordance with previous studies 16,26,27 which demonstrated that SS showed the lowest frictional coefficient and the lowest sliding resistance when used in passive configuration, which could be attributed its low roughness, high hardness and high strength. On the other hand, these data are in contrast with those of Farronato G et al 28 and Husmann et al 29 who detected that Teflon coated wires generated lower frictional forces compared to their corresponding uncoated wires.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study showed that the highest surface roughness was noted with Tefloncoated NiTi, followed by NiTi and CuNiTi, while the lowest surface roughness was noted for SS. These findings are in accordance with previous studies 16,26,27 which demonstrated that SS showed the lowest frictional coefficient and the lowest sliding resistance when used in passive configuration, which could be attributed its low roughness, high hardness and high strength. On the other hand, these data are in contrast with those of Farronato G et al 28 and Husmann et al 29 who detected that Teflon coated wires generated lower frictional forces compared to their corresponding uncoated wires.…”
Section: Discussionsupporting
confidence: 93%
“…Lateral force microscopy (LFM) is an AFM technique that is used to identify the relative difference in surface friction. LFM is also known as friction force microscopy, as it measures the lateral bending of the cantilever depending on the frictional force acting on the tip 15. During scanning in the contact mode, the cantilever not only bends in the vertical direction along the surface as a result of repulsive Van der Waals interactions, but also undergoes lateral deformation.…”
Section: Introductionmentioning
confidence: 99%
“…This positive correlation suggests that surface roughness can be used as an evaluation marker, in place of the direct measurement of FF, when estimating the efficiency of orthodontic treatment. 17 The SEM evaluation showed that the Ti-Ni and Ti-Nb alloy wires had smoother surfaces than the Ti-Mo alloy wire, which had a rough surface with abundant scratches. These results were consistent with those for the FF of the three alloy wires.…”
Section: Discussionmentioning
confidence: 97%